Histopathological Outcomes in Women with High-Risk HPV Infections: A Focus on HPV 31 - Ozkan, Serap; Koc, Sevgi; Soykan, Yagmur; Kayali, Eda; Basaran, Derman (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVE: To evaluate the histopathological findings of patients with high-risk human papillomavirus (hr-HPV) positivity. STUDY DESIGN: This retrospective cohort study included 814 women aged 30–65 years who underwent colposcopic evaluation following a positive hr-HPV DNA result detected using the Hybrid Capture 2 test (Qiagen, Hilden, Germany). HPV genotyping and concurrent cervical cytology were performed for all participants. RESULTS: Among the cohort, 495 women were positive for HPV 16 and/or 18, while 319 had non-16/18 hr-HPV types with negative cervical cytology. Colposcopic biopsy was performed in 515 cases. The prevalence of cervical intraepithelial neoplasia grade 2 or higher (CIN2+) was significantly higher in women with HPV 16/18 and negative cytology (23.3%) compared to those with non-16/18 hr-HPV and negative cytology (3.8%) (p=0.001). In the subgroup with HPV 16/18 positivity, CIN2+ lesions were detected in 42.6% of women with LSIL and 21.2% of those with ASCUS cytology (p=0.043). Among patients with ASCUS cytology, CIN2+ was identified in 40% of those with HPV 31 and only 6.3% of those infected with other non-16/18/31 hr-HPV types (p=0.021). Among patients with non-16/18 HPV DNA types, regardless of cytology, there was no statistically significant difference in terms of CIN2+ lesions between those with HPV type 31 and those with other high-risk types (excluding HPV 16, 18, and 31). CONCLUSIONS: HPV 16/18 remains the highest-risk group regardless of cytology. Among non-16/18 HPV patients, no significant difference in CIN2+ risk was found between HPV 31 and other types overall. However, HPV 31 poses a higher risk in patients with ASCUS cytology, indicating the need for closer management in this subgroup. Therefore, a more individualized evaluation is recommended for non-16/18 HPV infections.